O uso do Instagram como ferramenta de marketing digital: uma análise da ótica de empreendedoras femininas na cidade de Manaus - Xavier, Gabriela Amazonas (Brasil, 2024)
With technological advances and the growth of social networks, digital marketing has become essential for the success of companies, especially in the context of female entrepreneurs. This study aims to analyze the impact of Instagram as a digital marketing tool for the optimization and sustainability of the businesses of female entrepreneurs in Manaus. The methodology adopted was qualitative and descriptive, using a multiple case study, with six entrepreneurs from Manaus who use Instagram to promote their businesses. Data were collected through an online questionnaire, with statements based on the Likert scale, in addition to a discursive question about the perspective of Instagram's contribution to business profitability. The research concludes that Instagram plays a crucial role in the empowerment of female entrepreneurs and in the optimization of their businesses, providing a direct channel for effective communication and marketing. This study offers valuable contributions to the understanding of the impact of Instagram on female entrepreneurship, especially in the context of Manaus, and highlights the relevance of this platform for the sustainability and growth of businesses led by women.